Additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramic
Through photocuring additive manufacturing and ultra-fast high-temperature sintering technology, high-toughness alumina whisker toughened zirconia ceramics were prepared, which solved the problem of insufficient toughness of ceramics and long process, and achieved high density and high fracture toughness of ceramics .
Patent Information
- Application Number
- CN202411703314.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing zirconia ceramics are not tough enough, and the traditional degreasing and sintering processes take a long time, making it difficult to prepare complex ceramic components.
High-toughness alumina whisker toughened zirconia ceramics are prepared based on photocuring additive manufacturing technology and ultra-fast high-temperature sintering technology. Specific steps include preparing well-dispersed photocured ceramic slurry, preparing green bodies by 3D printing, thermal degreasing and ultra-fast high-temperature sintering.
The uniform dispersion of alumina whiskers in the zirconia matrix is achieved, the density and fracture toughness of the ceramic are improved, the process flow is simplified, and the production cost is reduced.
Smart Images

Figure CN119462137A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molding method of whisker toughened zirconia ceramics. Background Art
[0002] Partially stabilized zirconia polycrystalline ceramics with tetragonal phase as the main phase can overcome the inherent brittleness of ceramics to a certain extent due to the phase transformation toughening effect. At the same time, they have good wear resistance, chemical stability, biocompatibility, etc., and have been widely used in various structural and functional devices.
[0003] However, the toughness of the zirconia ceramics currently used is still insufficient. Further improvement of fracture toughness depends on the synergistic effect of multiple toughening mechanisms. Adding second-phase whiskers is a powerful means to improve the toughness of ceramic materials. Benefiting from whisker pull-out and crack deflection, bifurcation, and bridging, the composite material with added whiskers has significantly better mechanical properties than single-phase materials. Among various whiskers, alumina whiskers have similar strength and higher modulus, and have good matching with zirconia. As an oxide, they have the same high-temperature oxidation resistance as zirconia, making them a strong candidate as zirconia ceramic reinforcement.
[0004] CN108749040A discloses a zirconia toughened alumina ceramic-wear-resistant resin composite material and its preparation method. The use of wear-resistant resin improves the toughness of the material, but it cannot be applied to working conditions with more stringent strength and service temperature requirements. CN115010487A discloses a method for preparing whisker-toughened zirconia ceramics. Although it uses revolution and rotation stirring to avoid the breakage of whiskers during ball milling, it does not solve the initial dispersion problem of whiskers, and the dry pressing molding method cannot prepare complex ceramic components. CN117383914A discloses a method for preparing nano-zirconia toughened nano-alumina ceramics. It uses injection molding to directly prepare nano-zirconia toughened nano-alumina ceramic parts with final shape and high dimensional accuracy, but it still requires molds and the degreasing and sintering steps require a lot of man-hours. The final toughness of zirconia particles toughening alumina is also insufficient. Additive manufacturing technology based on a binder system can significantly reduce the preparation cycle and cost of complex ceramic components. However, the difficulty in introducing whiskers lies in the fact that whiskers are difficult to disperse evenly in the raw material system, whiskers make it difficult to densify ceramics, and traditional degreasing and sintering processes are too time-consuming. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for realizing rapid additive manufacturing of high-toughness alumina whisker-toughened zirconia ceramics based on photocuring additive manufacturing technology and ultra-fast high-temperature sintering technology.
[0006] A method for additive manufacturing of high-toughness alumina whisker toughened zirconia ceramics is specifically completed in the following steps:
[0007] 1. Preparation of slurry:
[0008] ①. Add alumina whiskers and dispersant into water and stir them ultrasonically for a period of time. After the dispersion is completed, add part of stabilized zirconium oxide and dispersant and stir them ultrasonically for a period of time to obtain a mixed powder slurry.
[0009] ②, placing the mixed powder slurry into a vacuum freezer for vacuum rapid freezing, and then performing vacuum freeze drying to obtain a mixed powder of alumina whiskers and partially stabilized zirconia;
[0010] ③, weigh 40-45 parts of alumina whiskers and partially stabilized zirconium oxide mixed powder and 55-60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing;
[0011] 2. Green printing:
[0012] ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body;
[0013] ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body;
[0014] 3. Degreasing and sintering:
[0015] ①, thermally degreasing the green body after secondary curing to obtain a semi-degreasing green body;
[0016] ②. Transfer the semi-degreased green body to an ultra-fast high-temperature sintering furnace, and sinter it at a preset current for a preset time to obtain a high-toughness alumina whisker-toughened zirconia ceramic.
[0017] The present invention has the following beneficial effects:
[0018] (1) The pre-dispersion, freeze-drying and non-contact stirring steps included in the present invention can prepare a light-cured ceramic slurry with good dispersion of aluminum oxide whiskers and good printability without destroying the whiskers;
[0019] (2) The non-reactive diluent added to the resin formula of the present invention not only acts as a thermoplastic resin solvent, but also can be discharged at a lower temperature, thereby forming uniform pore channels in the matrix, which is beneficial to the subsequent discharge of the pyrolysis gas of the resin and reduces the generation of defects;
[0020] (3) The thermoplastic polyimide added to the resin formula of the present invention is resistant to high temperatures and can be retained until the sintering stage and improve the high-temperature toughness of the green body, thereby preventing the semi-degreased green body from breaking during the ultra-fast high-temperature sintering process;
[0021] (4) The present invention uses semi-degreased green compacts to directly perform ultra-fast high-temperature sintering, so that the degreasing and sintering of the latter half can be completed simultaneously, thereby improving manufacturing efficiency;
[0022] (5) The rapid temperature rise and fall and instantaneous ultra-high temperature characteristics of ultra-fast high-temperature sintering can reduce the occurrence of abnormally grown grains, achieve the densification of alumina whisker-toughened zirconia ceramics that is difficult to achieve with conventional pressureless sintering, and reduce the generation of monoclinic zirconia;
[0023] (6) Short-term high-temperature sintering can inhibit the transformation of whiskers into rods / round crystals based on diffusion, and maintain the dispersed distribution of whiskers in the matrix;
[0024] (7) Based on the above beneficial effects, the density of the high-toughness alumina whisker toughened zirconia ceramic prepared by the present invention reaches 96.2%, and the fracture toughness reaches 15.3 MPa·m 1 / 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a surface SEM image of the high-toughness alumina whisker toughened zirconia ceramic prepared in Example 1;
[0026] Figure 2 This is a surface SEM image of the alumina whisker toughened zirconia ceramic prepared in Comparative Example 1;
[0027] Figure 3 The XRD diagrams of the alumina whisker toughened zirconia ceramics prepared in Example 1 and Comparative Example 1 are compared;
[0028] Figure 4 This is a surface SEM image of the zirconia ceramic prepared in Comparative Example 2;
[0029] Figure 5 This is a surface SEM image of the zirconia ceramic prepared in Comparative Example 3;
[0030] Figure 6 This is a side SEM image of the alumina whisker toughened zirconia degreased blank prepared in Comparative Example 4;
[0031] Figure 7 This is a side SEM image of the alumina whisker toughened zirconia ceramic prepared in comparative example five. DETAILED DESCRIPTION
[0032] Specific implementation method 1: This implementation method is an additive manufacturing method of high-toughness aluminum oxide whisker toughened zirconium oxide ceramics, which is specifically completed in the following steps:
[0033] 1. Preparation of slurry:
[0034] ①. Add alumina whiskers and dispersant into water and stir them ultrasonically for a period of time. After the dispersion is completed, add part of stabilized zirconium oxide and dispersant and stir them ultrasonically for a period of time to obtain a mixed powder slurry.
[0035] ②, placing the mixed powder slurry into a vacuum freezer for vacuum rapid freezing, and then performing vacuum freeze drying to obtain a mixed powder of alumina whiskers and partially stabilized zirconia;
[0036] ③, weigh 40-45 parts of alumina whiskers and partially stabilized zirconium oxide mixed powder and 55-60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing;
[0037] 2. Green printing:
[0038] ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body;
[0039] ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body;
[0040] 3. Degreasing and sintering:
[0041] ①, thermally degreasing the green body after secondary curing to obtain a semi-degreasing green body;
[0042] ②. Transfer the semi-degreased green body to an ultra-fast high-temperature sintering furnace, and sinter it at a preset current for a preset time to obtain a high-toughness alumina whisker-toughened zirconia ceramic.
[0043] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that: the diameter of the aluminum oxide whisker described in step 1① is 300nm~500nm, and the length is 10μm~20μm; the partially stabilized zirconium oxide described in step 1① is 3mol% yttria partially stabilized zirconium oxide, D 50 =500nm~700nm; the mass ratio of the aluminum oxide whiskers to the partially stabilized zirconium oxide in step 1① is 5:95; the solid content of the mixed powder slurry in step 1① is 10vol.%~20vol.%. The other steps are the same as the specific implementation method 1.
[0044] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the dispersant described in step 1① is one or both of polyethylene glycol 400 and polyethylene glycol 1000; the amount of dispersant added each time is 1% to 2% of the mass of the powder added at that time, and the ultrasonic stirring time is 30 minutes to 60 minutes. The other steps are the same as specific implementation method 1 or 2.
[0045] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the vacuum rapid freezing temperature in step 1 ② is -55°C, the time is 20min to 40min, the vacuum freeze drying temperature is -55°C, the vacuum degree is 1Pa, and the time is 22h to 24h. The other steps are the same as those of specific embodiments 1 to 3.
[0046] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the photosensitive resin described in step 1③ is composed of a monomer mixture, a dispersant, a non-reactive diluent, a thermoplastic resin and a photoinitiator; the mass ratio of the monomer mixture, the dispersant, the non-reactive diluent, the thermoplastic resin and the photoinitiator in the photosensitive resin is 60:(20-26):30:10:(1.2-1.3). The other steps are the same as those of specific embodiments 1 to 4.
[0047] Specific implementation six: This implementation is different from specific implementations one to five in that: the monomer mixture described in step one (3) is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate, wherein the mass ratio of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate is 30:10:20; the non-reactive diluent is polypropylene glycol 400; the thermoplastic resin is BASF Matrimid5218 soluble polyimide; the dispersant is one or more of BYK-103, BYK-110 and BYK-111; the photoinitiator is phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. The other steps are the same as those of specific implementations one to five.
[0048] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the stirring speed of the high-speed stirring and mixing in step 1 ③ is 1400 r / min to 2000 r / min, and the stirring time is 15 min to 30 min. The other steps are the same as those of specific embodiments 1 to 6.
[0049] Specific embodiment 8: The difference between this embodiment and specific embodiments 1 to 7 is that the slice thickness described in step 2① is 20μm; the wavelength of the ultraviolet light described in step 2② is 405nm, and the exposure energy is 12.6-24.4mW / cm2 , the exposure time is 1 to 4 seconds; the resin monomer in step 2② is hydroxyethyl acrylate, hydroxyethyl methacrylate or 1,6-hexanediol diacrylate; the number of cleanings is 1 to 2 times. The other steps are the same as those in specific embodiments 1 to 7.
[0050] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the process of thermal debinding described in step 3① is: placing the green body after secondary curing in a debinding furnace, evacuating to below 10Pa, and then introducing 99.999% high-purity nitrogen to normal pressure, and maintaining a nitrogen flow rate of 50mL / min, starting heating, heating to 145℃ at 1℃ / min and keeping warm for 60min, heating to 265℃ at 1℃ / min and keeping warm for 60min, heating to 320℃ at 1℃ / min and keeping warm for 60min, and cooling to room temperature at 1℃ / min. The other steps are the same as those of specific embodiments 1 to 8.
[0051] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that the sintering process described in step 3 ② is: using carbon felt as a heating body, placing the semi-degreased green body in the carbon felt interlayer in edge contact, and starting sintering with argon as a protective atmosphere; the current is 20A to 30A, and the holding time is 60s to 120s; the high-toughness alumina whisker toughened zirconia ceramic described in step 3 ② can reach a density of 96.2%, and the fracture toughness can reach 15.3MPa·m 1 / 2 The other steps are the same as those in Specific Embodiments 1 to 9.
[0052] The following examples are used to verify the beneficial effects of the present invention:
[0053] Embodiment 1: An additive manufacturing method for high-toughness alumina whisker toughened zirconia ceramics is specifically completed in the following steps:
[0054] 1. Preparation of slurry:
[0055] ①, weigh 5 parts of aluminum oxide whiskers, 0.05 parts of polyethylene glycol 400, 95 parts of partially stabilized zirconium oxide and 0.95 parts of polyethylene glycol 400 by weight; add 5 parts of aluminum oxide whiskers and 0.05 parts of polyethylene glycol 400 into water and stir ultrasonically for 30 minutes, after dispersion is completed, add 95 parts of partially stabilized zirconium oxide and 0.95 parts of polyethylene glycol 400, stir ultrasonically for 30 minutes to obtain a mixed powder slurry;
[0056] The solid content of the mixed powder slurry described in step 1① is 15 vol.%;
[0057] The diameter of the aluminum oxide whisker described in step 1① is 300nm~500nm, and the length is 10μm~20μm;
[0058] The partially stabilized zirconium oxide described in step 1① is 3 mol% yttria partially stabilized zirconium oxide, D 50 =500nm~700nm;
[0059] ②, put the mixed powder slurry into a vacuum freezer and start to draw vacuum and freeze at -55°C for 30 minutes, then freeze-dry at -55°C and vacuum degree 1Pa for 24 hours to obtain a mixed powder of alumina whiskers and partially stabilized zirconia;
[0060] ③, weigh 40 parts of alumina whiskers and partially stabilized zirconium oxide mixed powder and 60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing;
[0061] The photosensitive resin described in step 1③ is composed of a monomer mixture, a dispersant, a non-reactive diluent, a thermoplastic resin and a photoinitiator; the mass ratio of the monomer mixture, the dispersant, the non-reactive diluent, the thermoplastic resin and the photoinitiator in the photosensitive resin is 60:20:30:10:1.2;
[0062] The monomer mixture described in step 1③ is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate, wherein the mass ratio of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate is 30:10:20; the non-reactive diluent is polypropylene glycol 400; the thermoplastic resin is BASF Matrimid 5218 soluble polyimide; the dispersant is BYK-111; the photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide;
[0063] The stirring speed of the high-speed stirring mixing described in step 1③ is 1400r / min, and the stirring time is 30min;
[0064] 2. Green printing:
[0065] ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body;
[0066] The slice thickness described in step 2① is 20 μm;
[0067] ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body;
[0068] The wavelength of the ultraviolet light described in step 2② is 405nm, and the exposure energy is 12.6mW / cm 2 , the exposure time is 3s;
[0069] The resin monomer described in step 2② is 1,6-hexanediol diacrylate, and the number of washings is 2 times;
[0070] 3. Degreasing and sintering:
[0071] ①, thermally degreasing the green body after secondary curing to obtain a semi-degreasing green body;
[0072] The process of thermal debinding described in step 3① is as follows: placing the green body after secondary curing in a debinding furnace, evacuating to below 10Pa, and then introducing 99.999% high-purity nitrogen to normal pressure, and maintaining a nitrogen flow rate of 50mL / min, starting heating, heating to 145°C at 1°C / min and keeping warm for 60min, heating to 265°C at 1°C / min and keeping warm for 60min, heating to 320°C at 1°C / min and keeping warm for 60min, and cooling to room temperature at 1°C / min;
[0073] ②. Transfer the semi-degreased green body to an ultra-fast high-temperature sintering furnace, and sinter it at a preset current for a preset time to obtain a high-toughness alumina whisker-toughened zirconia ceramic.
[0074] The sintering process described in step 3② is: using carbon felt as a heating body, placing the semi-degreased green body in the carbon felt interlayer in an edge-contact form, and starting sintering with argon as a protective atmosphere; the current is 26A, and the holding time is 90s;
[0075] The size of the high-toughness alumina whisker toughened zirconia ceramic described in step 3② is 2mm×4mm×20mm.
[0076] Figure 1 This is a surface SEM image of the high-toughness alumina whisker toughened zirconia ceramic prepared in Example 1;
[0077] from Figure 1 It can be seen that the high-toughness alumina whisker toughened zirconia ceramic prepared in Example 1 has a high degree of densification, and the alumina whiskers are evenly dispersed in the zirconia matrix; the density measured by the Archimedes method is 96.2%, and the fracture toughness measured by the single-edge notched beam method is 15.3 MPa·m 1 / 2 .
[0078] Comparative Example 1: A method for preparing alumina whisker toughened zirconia ceramics is specifically completed in the following steps:
[0079] 1. Preparation of slurry:
[0080] ①, weigh 5 parts of aluminum oxide whiskers, 0.05 parts of polyethylene glycol 400, 95 parts of partially stabilized zirconium oxide and 0.95 parts of polyethylene glycol 400 by weight; add 5 parts of aluminum oxide whiskers and 0.05 parts of polyethylene glycol 400 into water and stir ultrasonically for 30 minutes, after dispersion is completed, add 95 parts of partially stabilized zirconium oxide and 0.95 parts of polyethylene glycol 400, stir ultrasonically for 30 minutes to obtain a mixed powder slurry;
[0081] The solid content of the mixed powder slurry described in step 1① is 15 vol.%;
[0082] The diameter of the aluminum oxide whisker described in step 1① is 300nm~500nm, and the length is 10μm~20μm; step 1
[0083] The partially stabilized zirconium oxide described in ① is 3 mol % yttria partially stabilized zirconium oxide,
[0084] D 50 =500nm~700nm;
[0085] ② Place the mixed powder slurry in an air oven at 70°C and dry for 12 hours to obtain a mixed powder;
[0086] ③, weigh 40 parts of alumina whiskers and partially stabilized zirconium oxide mixed powder and 60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing;
[0087] The photosensitive resin described in step 1③ is composed of a monomer mixture, a dispersant, a non-reactive diluent, a thermoplastic resin and a photoinitiator; the mass ratio of the monomer mixture, the dispersant, the non-reactive diluent, the thermoplastic resin and the photoinitiator in the photosensitive resin is 60:20:30:10:1.2;
[0088] The monomer mixture described in step 1③ is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate, wherein the mass ratio of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate is 30:10:20; the non-reactive diluent is polypropylene glycol 400; the thermoplastic resin is BASF Matrimid 5218 soluble polyimide; the dispersant is BYK-111; the photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide;
[0089] The stirring speed of the high-speed stirring mixing described in step 1③ is 1400r / min, and the stirring time is 30min;
[0090] 2. Green printing:
[0091] ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body;
[0092] The slice thickness described in step 2① is 20 μm;
[0093] ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body;
[0094] The wavelength of the ultraviolet light described in step 2② is 405nm, and the exposure energy is 12.6mW / cm 2 , the exposure time is 3s;
[0095] The resin monomer described in step 2② is 1,6-hexanediol diacrylate, and the number of washings is 2 times;
[0096] 3. Degreasing and sintering:
[0097] ①, thermally debind the green body after secondary curing to obtain a crack-free debind body;
[0098] The process of thermal degreasing described in step 3① is: placing the green body after secondary curing in a degreasing furnace, evacuating to below 10Pa, and then introducing 99.999% high-purity nitrogen to normal pressure, and maintaining a nitrogen flow rate of 50mL / min, starting heating, heating to 145°C at 1°C / min and keeping warm for 60min, heating to 265°C at 1°C / min and keeping warm for 60min, heating to 320°C at 1°C / min and keeping warm for 60min, heating to 385°C at 1°C / min and keeping warm for 60min, heating to 450°C at 1°C / min and keeping warm for 60min, heating to 485°C at 1°C / min and keeping warm for 60min, heating to 525°C at 1°C / min and keeping warm for 60min, heating to 595°C at 1°C / min and keeping warm for 60min, cooling to room temperature at 1°C / min to obtain a degreased green body without cracking;
[0099] ②, sintering the crack-free degreased body to obtain alumina whisker-toughened zirconia ceramics;
[0100] The sintering described in step three ② is divided into two stages: the first stage is pre-sintering: the crack-free degreased body is placed in a sintering furnace, using a normal pressure air atmosphere and maintaining an air flow rate of 100 mL / min, and heating is started, heating to 600°C at 1°C / min, heating to 950°C at 5°C / min and keeping warm for 120 minutes, and the second stage is sintering: heating to 1500°C at 5°C / min and keeping warm for 2 hours, and cooling to room temperature at 5°C / min, and finally obtaining alumina whisker toughened zirconia ceramics.
[0101] Figure 2 This is a surface SEM image of the alumina whisker toughened zirconia ceramic prepared in Comparative Example 1;
[0102] from Figure 2 It can be seen that some whiskers are agglomerated and there are a lot of pores at the agglomeration sites. It can also be seen that the whiskers are significantly coarsened due to long-term high-temperature sintering. The density measured by the Archimedes method is 92.1%, and the fracture toughness measured by the single-edge notched beam method is 9.1 MPa·m 1 / 2 .
[0103] Figure 3 The XRD diagrams of the alumina whisker toughened zirconia ceramics prepared in Example 1 and Comparative Example 1 are compared;
[0104] from Figure 3 It can be seen that the alumina whisker toughened zirconia ceramics prepared by the traditional pressureless sintering method contain a small amount of m-phase zirconia, while the samples prepared by ultra-rapid high temperature sintering reduce the transformation of m-phase to t-phase during the cooling process due to the rapid cooling, which further improves the performance.
[0105] Comparative Example 2: The difference between this embodiment and the embodiment 1 is that: in step 1①, 0 parts of aluminum oxide whiskers and 100 parts of partially stabilized zirconium oxide are weighed by weight; 0 parts of aluminum oxide whiskers and 100 parts of partially stabilized zirconium oxide are added to water and ultrasonically stirred for 30 minutes to obtain zirconium oxide powder slurry; the final product is zirconium oxide ceramic. The other steps and parameters are the same as those of the embodiment 1.
[0106] Figure 4 This is a surface SEM image of the zirconia ceramic prepared in Comparative Example 2;
[0107] from Figure 4 It can be seen that the grain size is relatively uniform, the density measured by the Archimedes method is 98.9%, and the fracture toughness measured by the single-edge notched beam method is 11.2 MPa·m 1 / 2 .
[0108] Comparative Example 3: The process of preparing zirconia ceramics by using the traditional degreasing and sintering process is specifically completed in the following steps:
[0109] 1. Preparation of slurry:
[0110] ①, weighing 0 parts of aluminum oxide whiskers and 100 parts of partially stabilized zirconium oxide by weight; adding 0 parts of aluminum oxide whiskers and 100 parts of partially stabilized zirconium oxide into water and stirring ultrasonically for 30 minutes to obtain zirconium oxide powder slurry;
[0111] The solid content of the zirconium oxide powder slurry described in step 1① is 15 vol.%;
[0112] The partially stabilized zirconium oxide in step 1① is 3 mol % yttria partially stabilized zirconium oxide,
[0113] D 50 =500nm~700nm;
[0114] ② Place the zirconium oxide powder slurry in an air oven at 70°C and dry for 12 hours to obtain powder;
[0115] ③. Weigh 40 parts of dried partially stabilized zirconium oxide powder and 60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing;
[0116] The photosensitive resin described in step 1③ is composed of a monomer mixture, a dispersant, a non-reactive diluent, a thermoplastic resin and a photoinitiator; the mass ratio of the monomer mixture, the dispersant, the non-reactive diluent, the thermoplastic resin and the photoinitiator in the photosensitive resin is 60:20:30:10:1.2;
[0117] The monomer mixture described in step 1③ is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate, wherein the mass ratio of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate is 30:10:20; the non-reactive diluent is polypropylene glycol 400; the thermoplastic resin is BASF Matrimid 5218 soluble polyimide; the dispersant is BYK-111; the photoinitiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide;
[0118] The stirring speed of the high-speed stirring mixing described in step 1③ is 1400r / min, and the stirring time is 30min;
[0119] 2. Green printing:
[0120] ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body;
[0121] The slice thickness described in step 2① is 20 μm;
[0122] ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body;
[0123] The wavelength of the ultraviolet light described in step 2② is 405nm, and the exposure energy is 12.6mW / cm 2 , the exposure time is 3s;
[0124] The resin monomer described in step 2② is 1,6-hexanediol diacrylate, and the number of washings is 2 times;
[0125] 3. Degreasing and sintering:
[0126] ①, thermally debind the green body after secondary curing to obtain a crack-free debind body;
[0127] The process of thermal degreasing described in step 3① is: placing the green body after secondary curing in a degreasing furnace, evacuating to below 10Pa, and then introducing 99.999% high-purity nitrogen to normal pressure, and maintaining a nitrogen flow rate of 50mL / min, starting heating, heating to 145°C at 1°C / min and keeping warm for 60min, heating to 265°C at 1°C / min and keeping warm for 60min, heating to 320°C at 1°C / min and keeping warm for 60min, heating to 385°C at 1°C / min and keeping warm for 60min, heating to 450°C at 1°C / min and keeping warm for 60min, heating to 485°C at 1°C / min and keeping warm for 60min, heating to 525°C at 1°C / min and keeping warm for 60min, heating to 595°C at 1°C / min and keeping warm for 60min, cooling to room temperature at 1°C / min to obtain a degreased green body without cracking;
[0128] ②, sintering the crack-free degreased body to obtain zirconia ceramics;
[0129] The sintering described in step three ② is divided into two stages: the first stage is pre-sintering: the crack-free degreased body is placed in a sintering furnace, using a normal pressure air atmosphere and maintaining an air flow rate of 100 mL / min, starting heating, heating to 600°C at 1°C / min, heating to 950°C at 5°C / min and keeping warm for 120 minutes, and the second stage is sintering: heating to 1500°C at 5°C / min and keeping warm for 2 hours, cooling to room temperature at 5°C / min, and finally obtaining zirconia ceramics.
[0130] Figure 5 This is a surface SEM image of the zirconia ceramic prepared in Comparative Example 3;
[0131] from Figure 5 It can be seen that there are many abnormally grown grains.
[0132] Comparative Example 4: The difference between this example and Example 1 is that the non-reactive diluent is omitted and the same mass of mixed monomer is used instead. The other steps and parameters are the same as those of Example 1.
[0133] Figure 6 This is a side SEM image of the alumina whisker toughened zirconia degreased blank prepared in Comparative Example 4;
[0134] from Figure 6 It can be seen that due to the lack of non-reactive diluent, more resin pyrolysis gas is discharged under the same debinding process, resulting in the generation of cracks.
[0135] Comparative Example 5: The difference between this example and the first example is that the thermoplastic polyimide is omitted and a monomer mixture of the same mass is used instead. The other steps and parameters are the same as those of the first example.
[0136] Figure 7 This is a side SEM image of the alumina whisker toughened zirconia ceramic prepared in Comparative Example 5;
[0137] from Figure 7 It can be seen that due to the lack of thermoplastic polyimide, the toughness of the semi-debinded green body is insufficient, and delamination occurs during ultra-rapid high-temperature sintering.
Claims
1. A method for additive manufacturing of high-toughness alumina whisker toughened zirconia ceramics, characterized in that The method is specifically completed according to the following steps:
1. Preparation of slurry: ①. Add alumina whiskers and dispersant into water and stir them ultrasonically for a period of time. After the dispersion is completed, add part of stabilized zirconium oxide and dispersant and stir them ultrasonically for a period of time to obtain a mixed powder slurry. ②, placing the mixed powder slurry into a vacuum freezer for vacuum rapid freezing, and then performing vacuum freeze drying to obtain a mixed powder of alumina whiskers and partially stabilized zirconia; ③, weigh 40-45 parts of alumina whiskers and partially stabilized zirconium oxide mixed powder and 55-60 parts of photosensitive resin by weight, stir and mix them at high speed in a planetary degassing mixer for a period of time to obtain a photocurable ceramic slurry that can be used for printing; 2. Green printing: ① First, build a model through CAD software and convert it into an STL format file. Then import the STL format file into the 3D printing device and set the slice thickness. Use the surface exposure projection method to print the light-cured ceramic slurry to obtain a green body; ②, using a resin monomer to clean the green body, air-drying the green body and then performing secondary curing under ultraviolet light to obtain a secondary cured green body; 3. Degreasing and sintering: ①, thermally degreasing the green body after secondary curing to obtain a semi-degreasing green body; ②. Transfer the semi-degreased green body to an ultra-fast high-temperature sintering furnace, and sinter it at a preset current for a preset time to obtain a high-toughness alumina whisker-toughened zirconia ceramic.
2. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The diameter of the aluminum oxide whisker in step 1① is 300nm to 500nm, and the length is 10μm to 20μm; the partially stabilized zirconium oxide in step 1① is 3mol% yttria partially stabilized zirconium oxide, D 50 =500nm~700nm; the mass ratio of the alumina whiskers to the partially stabilized zirconia described in step 1① is 5:95; the solid content of the mixed powder slurry described in step 1① is 10vol.%~20vol.%.
3. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The dispersant described in step 1① is one or both of polyethylene glycol 400 and polyethylene glycol 1000; the amount of dispersant added each time is 1% to 2% of the mass of the powder added at that time, and the ultrasonic stirring time is 30min to 60min.
4. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The temperature of the vacuum rapid freezing described in step 1② is -55°C, the time is 20min to 40min, and the temperature of the vacuum freeze drying is -55°C, the vacuum degree is 1Pa, and the time is 22h to 24h.
5. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The photosensitive resin described in step 1③ is composed of a monomer mixture, a dispersant, a non-reactive diluent, a thermoplastic resin and a photoinitiator; the mass ratio of the monomer mixture, the dispersant, the non-reactive diluent, the thermoplastic resin and the photoinitiator in the photosensitive resin is 60:(20-26):30:10:(1.2-1.3).
6. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 5, characterized in that The monomer mixture described in step 1③ is a mixture of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate, wherein the mass ratio of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate and o-phenylphenoxyethyl acrylate is 30:10:20; the non-reactive diluent is polypropylene glycol 400; the thermoplastic resin is a soluble polyimide; the dispersant is one or more of BYK-103, BYK-110 and BYK-111; the photoinitiator phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.
7. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The stirring speed of the high-speed stirring and mixing described in step 1③ is 1400r / min~2000r / min, and the stirring time is 15min~30min.
8. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The slice thickness in step 2① is 20 μm; the wavelength of the ultraviolet light in step 2② is 405 nm, and the exposure energy is 12.6 to 24.4 mW / cm 2 , the exposure time is 1 to 4 seconds; the resin monomer described in step 2② is hydroxyethyl acrylate, hydroxyethyl methacrylate or 1,6-hexanediol diacrylate; the number of cleanings is 1 to 2 times.
9. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The thermal debinding process described in step 3① is as follows: place the green body after secondary curing in a debinding furnace, evacuate to below 10Pa, and then introduce 99.999% high-purity nitrogen to normal pressure, and maintain a nitrogen flow rate of 50mL / min, start heating, heat to 145℃ at 1℃ / min and keep warm for 60min, heat to 265℃ at 1℃ / min and keep warm for 60min, heat to 320℃ at 1℃ / min and keep warm for 60min, and cool to room temperature at 1℃ / min.
10. The additive manufacturing method of high-toughness alumina whisker toughened zirconia ceramics according to claim 1, characterized in that The sintering process described in step 3② is as follows: using carbon felt as a heating body, placing the semi-degreased green body in the carbon felt interlayer in an edge-contact form, and starting sintering with argon as a protective atmosphere; the current is 20A to 30A, and the holding time is 60s to 120s; the high-toughness alumina whisker toughened zirconia ceramic described in step 3② can reach a density of 96.2% and a fracture toughness of 15.3MPa·m 1 / 2 .
Citation Information
Patent Citations
Zirconia toughened alumina ceramic and abrasion proof resin composite material and preparation method thereof
CN108749040A
Preparation method of whisker toughened zirconia ceramic
CN115010487A
Preparation method of nano-zirconia toughened nano-alumina ceramic
CN117383914A
3D printing molding material
CN108178659A
Silicon carbide whisker-toughened aluminum oxide composite ceramic material for bulletproof armor and preparation method thereof
CN111995413A
Cited By
Stable zirconia high-toughness ceramic and preparation method thereof
CN120247553A
ZTA ceramic powder, ceramic substrate and preparation method thereof
CN121318399A
ZTA ceramic powder, ceramic substrate and preparation method thereof
CN121318399B